5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21

Simple and best practice solution for 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 equation:


Simplifying
5(3x + -1) + 2x + 9(2x + -3) = 5(6x + -7) + 11x + -21

Reorder the terms:
5(-1 + 3x) + 2x + 9(2x + -3) = 5(6x + -7) + 11x + -21
(-1 * 5 + 3x * 5) + 2x + 9(2x + -3) = 5(6x + -7) + 11x + -21
(-5 + 15x) + 2x + 9(2x + -3) = 5(6x + -7) + 11x + -21

Reorder the terms:
-5 + 15x + 2x + 9(-3 + 2x) = 5(6x + -7) + 11x + -21
-5 + 15x + 2x + (-3 * 9 + 2x * 9) = 5(6x + -7) + 11x + -21
-5 + 15x + 2x + (-27 + 18x) = 5(6x + -7) + 11x + -21

Reorder the terms:
-5 + -27 + 15x + 2x + 18x = 5(6x + -7) + 11x + -21

Combine like terms: -5 + -27 = -32
-32 + 15x + 2x + 18x = 5(6x + -7) + 11x + -21

Combine like terms: 15x + 2x = 17x
-32 + 17x + 18x = 5(6x + -7) + 11x + -21

Combine like terms: 17x + 18x = 35x
-32 + 35x = 5(6x + -7) + 11x + -21

Reorder the terms:
-32 + 35x = 5(-7 + 6x) + 11x + -21
-32 + 35x = (-7 * 5 + 6x * 5) + 11x + -21
-32 + 35x = (-35 + 30x) + 11x + -21

Reorder the terms:
-32 + 35x = -35 + -21 + 30x + 11x

Combine like terms: -35 + -21 = -56
-32 + 35x = -56 + 30x + 11x

Combine like terms: 30x + 11x = 41x
-32 + 35x = -56 + 41x

Solving
-32 + 35x = -56 + 41x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-41x' to each side of the equation.
-32 + 35x + -41x = -56 + 41x + -41x

Combine like terms: 35x + -41x = -6x
-32 + -6x = -56 + 41x + -41x

Combine like terms: 41x + -41x = 0
-32 + -6x = -56 + 0
-32 + -6x = -56

Add '32' to each side of the equation.
-32 + 32 + -6x = -56 + 32

Combine like terms: -32 + 32 = 0
0 + -6x = -56 + 32
-6x = -56 + 32

Combine like terms: -56 + 32 = -24
-6x = -24

Divide each side by '-6'.
x = 4

Simplifying
x = 4

See similar equations:

| 4(-x-2)= | | 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 | | -2y-42=-4(y+7) | | -2(y+9)= | | 5(c+2)=25 | | .4(12n-8)=26 | | 4(2x-7)=3(x+4) | | 2b+12b=70 | | 13x+(x+3)+(x+2)+(x+7)=40 | | 6x^3-5x^2+1=0 |

Equations solver categories